CROSS-SECTOR COLLABORATION IN THE LIPA SABBE' WOVEN FABRIC INDUSTRY IN SOUTH SULAWESI - Al-Fatiha, Aurora Ramadhani Putri; Rukmana, Novayanti Sopia; Purna, Zarni Adia (Jurnal Aktor, 2025)
This study aims to see whether Sustainable Supply Chain Governance can maintain the sustainability of the lipa sabbe' woven silk industry in South Sulawesi and to describe the collaboration that occurs in both cross-sectors in maintaining the sustainability of the lipa sabbe' woven silk industry in South Sulawesi. The data validity check was carried out by triangulating sources. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of the study indicate that cross-sector collaboration in the lipa sabbe' woven industry in South Sulawesi which makes Soppeng Regency the upstream sector and Wajo Regency the downstream sector in the large supply chain in fact does not collaborate with each other as key actors controlling the flow of the lipa sabbe' woven industry in South Sulawesi. The two regencies that exist in fact form their own industrial flows, thus creating aspects of regional competitiveness that threaten sustainability in the lipa sabbe' woven industry and do not create sustainable development in the large supply chain from upstream to downstream. The recommendation in this study is that the government is expected to be able to create coordination along the supply chain of the lipa sabbe' woven fabric industry through cooperation between governments so that the supply chain process runs systematically and collaborates with each other, thus creating efficient sustainable development in the lipa sabbe' woven fabric industry in South Sulawesi.